PENETAPAN AMBANG BATAS KADAR Fe TOTAL DALAM PUPUK ORGANIK YANG BERPOTENSI MENYEBABKAN KERACUNAN Fe TANAMAN PADI SAWAH - Cahyadi Cahyadi; Nia Yuliani; Srikandi Srikandi (JURNAL SAINS NATURAL, 2013)
Determination of Threshold Levels of Total Fe in Organic Fertilizer that Have Potential to Cause Fe Poisoning for Rice Plant         The type and quality of organic fertilizers on the market either already registered or not registered are huge numbers . The Government has issued a Ministerial Regulation of Agriculture no 28 in  2009 on organic fertilizers, bio-fertilizers , and soil repair is now revised to Regulation of the Minister of Agriculture no 70 in 2011, in order to have  a good quality of solid organic fertilizer that having  Fe content does not exceed 9,000 mg / kg . This study aims to establish the total Fe content in the organic fertilizer that could potentially lead then to Fe toxicity for rice plant. The results showed that the effect of organic fertilizer and Fe levels were not significantly different in plant height number,number of seedling, dry straw weight , C - Organic , cation exchange capacity (CEC) and the grain content , but significantly different in plant height and number of tillers at 20 days after plantation . Fe - toxicity limited the total solid organic fertilizer with a dose of 1 ton / ha causing toxicity to rice varieties IR 64 on the ground Inceptisol of  54,318 mg Fe/ kg . Threshold in Fe - organic fertilizer with a total dose of 1 ton / ha which could potentially lead to Fe deficiency IR 64 rice varieties at 12,682 mg Fe/ kg , whereas Fe toxicity level was equal to 54,318 mg Fe/ kg .Keywords : TotalFe content, organicfertilizer, toxicity, rice ABSTRAK          Jenis dan mutu pupuk organik yang beredar di pasaran baik yang sudah terdaftar maupun yang belum terdaftar jumlahnya sangat banyak.Pemerintah telah mengeluarkan Peraturan Menteri Pertanian No. 28 Tahun 2009 tentang pupuk organik, pupuk hayati, dan pembenah tanah yang saat ini sudah direvisi menjadi Peraturan Menteri Pertanian No. 70 Tahun 2011 bahwa agar pupuk organik padat berkualitas baik maka kadar Fe yang ada tidak melebihi 9.000 mg/kg. Penelitian ini bertujuan menetapkan kadar Fe total dalam pupuk organik yang berpotensi menyebabkan keracunan Fe untuk tanaman padi sawah. Hasil penelitian menunjukkan bahwa pengaruh pemberian pupuk organik dan kadar Fe tidak berbeda nyata pada tinggi tanaman, jumlah anakan, berat kering jerami, C-Organik, kapasitas tukar kation (KTK) dan isi gabah, tetapi berbeda nyata pada tinggi tanaman dan jumlah anakan pada 20 HST.   Batas toksisitas Fe-total dalam pupuk organik padat dengan dosis 1 ton/ha yang berpotensi menyebabkan keracunan Fe untuk tanaman padi varietas IR 64 pada tanah inceptisol sebesar 54.318 mg Fe/kg. Ambang batas Fe-total dalam pupuk organik dengan dosis 1 ton/ha yang berpotensi menyebabkan kekurangan Fe untuk tanaman padi varietas IR 64 sebesar 12.682 mg Fe/kg, sedangkan  tingkat keracunan Fe adalah sebesar 54.318 mg Fe/kg.Kata kunci : Kadar Fe total, pupuk organik, toksisitas, padi